Faktor-Faktor yang Mempengaruhi Konsumsi Sayur-Sayuran Di Kabupaten Hulu Sungai Utara Provinsi Kalimantan Selatan - Heldawati Heldawati (Rawa Sains: Jurnal Sains STIPER Amuntai, 2016)
This study aims to measure the amount of consumption of household vegetables in rural and urban areas, and to analyze the factors that affect consumption of household vegetables in rural and urban areas in North Hulu Sungai Regency, South Kalimantan Province. The study was conducted in February - July 2014 in Central Amuntai Subdistrict by selecting three villages with rural criteria, namely Pinang Habang Village, Lake Carmin and Tigarun, and three villages with urban criteria namely Malang River, Upper Ulin and Downstream Turning Stairs. The multistage sampling method with random sampling is applied. Data analysis using multiple linear regression. The results showed that vegetable consumption in urban areas was greater than the consumption of vegetables in rural areas. Vegetable consumption in rural and urban areas in North Hulu Sungai is lower than the recommended nutritional standard of the government Food Pattern (PPH), which is 250 grams / capita / day. The factors that influence rural and urban vegetable consumption are ownership of households in the North River is family size, knowledge of maternal nutrition, preference for vegetables and regional typology (village / city). On the other hand, family income does not affect the consumption of household vegetables